Merkel cell carcinoma with axillary metastasis; a case report of a rare disease - Serdar Culcu; Aydan Eroglu; Aylin Heper (Journal of Oncological Sciences, 2018)
Merkel cell carcinoma is a rare primer neuroendocrine carcinoma of the skin. It is an extremely aggressive tumor. This rare carcinoma is seen with high local and regional recurrence ratios and distant metastasis. We report that a 64 years old female patient who had undergo an excision in another center because of a mass on 4 cm proximal of her right elbow had been diagnosed with Merkel cell carcinoma with positive surgical margins. She was treated with wide re-excision and axillary dissection at our clinic. Keywords: Merkel cell carcinoma, Skin, Axillary metastasis